Optimization of Drying Models for Various Types of Turmeric Using A Tray Dryer - Jassin, Ernawati; Fitri, Muhammad; Arisandi, Arwini; Aisyah, Nur (Journal of Agriculture, 2024)
Turmeric (Curcuma domestica val) is one of the plants that has benefits including as spices, seasonings, herbs, to maintain health and beauty and utilization as traditional medicine.  Drying is a method to extend the shelf life and maintain the quality of a post-harvest product before further processing. This study aims to optimize the thin layer drying model on various types of turmeric (white turmeric, black turmeric and yellow turmeric). Data obtained from drying results in the form of initial mass, mass during drying and the final mass of drying. Then processed to obtain the wet base moisture content, dry base moisture content and Moisture Ratio.  The thin layer drying model is obtained by finding the constant value of k, a and n from each exponential form. Determination of constants using Solver Tool Microsoft Excel that automatically searches for constant values in each dryer model tested, then obtains the highest R² value as the best model that describes the drying model of black turmeric and yellow turmeric. From the test results of curcumin content in white turmeric, black turmeric and yellow turmeric where the content of yellow turmeric has a higher value than both turmeric because it has an almost perfect arrangement of chemical elements. In the pH test, the highest result was obtained in white turmeric, namely 4.8 where the less curcumin contained in the turmeric rhizome, the higher the level of acidity of the turmeric.